TESTING THE BOUNDARIES OF LEAN SUPPLY CHAIN THINKING: OBSERVATIONS FROM THE LEGAL SECTOR - Hines, P.; Martins, A. (10th International Symposium on Logistics, 2005)
Supply Chain Management has attracted much academic attention over the last twenty years with a Lean Thinking approach being widely discussed over the last decade. However, in the majority of these cases the focus has been on the manufacturing industry. Scant attention has been directed to the service sector, which in many advanced economies represents around 70% of GDP. Within this, research into the public sector, outside of a procurement environment, is even rarer, although the public sector can represent well over 40% of total GDP in advanced economies. This paper seeks to review this service environment within the legal sector through two public sector cases from Portugal and Wales. It seeks to understand: whether there are any existing exemplars, how Lean Supply Chain Thinking may be taken into this sector, where would you start, what would you do and what modifications you may require to do this successfully. It will also provide a tentative Lean Legal Supply Chain Model and Route Plan for the sector.